Industry Guidelines for Seafood Health and Nutrition Messages - McManus, Alexandra; Nicholson, Claire (Centre of Excellence for Science Seafood & Health (CESSH), 2010)
This guide has been written to assist the seafood industry to recognise and promote health and nutrition messages regarding seafood consumption and health.The guide summarises relevant regulations, legislation and guidelines governing use of health and nutrition messages to promote seafood on food labels and in advertising material. Although this guide provides the main points that should be considered when promoting the health benefits of seafood, it is recommended that the original documents are referred to when planning any labelling or advertising materials. A list of relevant websites and references are provided at the end of this guide. The guide also summarises scientific evidence regarding the health benefits of seafood consumption.